2016
DOI: 10.1080/17448727.2016.1147174
|View full text |Cite
|
Sign up to set email alerts
|

Caste and Identity Processes among British Sikhs in the Midlands

Abstract: This article examines the role of caste in the lives and identities of a small sample of young Sikhs in the English Midlands, using social psychological theory. In many academic writings, there is an implicit representation of caste as a negative aspect of South Asian culture and religion, and of caste identification as a means of oppressing vulnerable outgroups. Twenty-three young Sikhs were interviewed, and the qualitative data were analysed using Identity Process Theory. The following themes are discussed: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…The findings of our research further confirm the complexity of how caste operates at a practical level amongst the Sikhs, specifically British Sikhs in the context of the research we undertook. Contrary to popular understandings of caste, identification with a caste is not synonymous with caste-based prejudice and discrimination (Jaspal and Takhar 2016).…”
Section: Legislation Against Caste Discrimination In the Uk Single Eqmentioning
confidence: 95%
See 2 more Smart Citations
“…The findings of our research further confirm the complexity of how caste operates at a practical level amongst the Sikhs, specifically British Sikhs in the context of the research we undertook. Contrary to popular understandings of caste, identification with a caste is not synonymous with caste-based prejudice and discrimination (Jaspal and Takhar 2016).…”
Section: Legislation Against Caste Discrimination In the Uk Single Eqmentioning
confidence: 95%
“…His argument largely focuses on the problematic issues relating to the legal framework within which the legislation is positioned.Interestingly, his discussion gives credence to the anti-caste-legislation attitudes and draws on extended ethnographic research on Hindu and Sikh perspectives. His work echoes a number of the concerns put forward by the Sikh Council UK in emphasizing that caste discrimination is not an issue in the UK (for a detailed insight into the Sikh Council UK's views, see Jaspaland Takhar 2016). Another report, which in many ways supports the Sikh Council's conviction that caste plays no role amongst British Sikhs, is the British Sikh Report (BSR) 2013 3 which has been produced annually since 2013 to provide an overview of the needs andchallenges faced by the British Sikh community.…”
mentioning
confidence: 90%
See 1 more Smart Citation
“…My analysis in the current article is therefore grounded in the existing literature on Punjabi masculinities and partly in Identity Process Theory. Identity Process Theory postulates various motivational principles that help guide identity construction in individuals (Breakwell, 1986; Jaspal, 2011; Jaspal & Takhar, 2016; Vignoles et al., 2000). Specifically, I delineate some of the guiding ‘identity principles’ as they are employable and seem relevant to the hegemonic principles of masculinities in a transnational context such as (i) continuity, (ii) distinctiveness and (iii) belonging (Jaspal & Takhar, 2016, p. 90; see also Jaspal, 2011).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The downward comparison principle, which is derived from SIT, suggests that individuals compare their ingroup with outgroups on dimensions in which they will perform favorably. For instance, in recent research into caste identity among Indians (Jaspal & Takhar, 2016), it was found that members of traditionally "lower" caste groups often accentuated tenets of their caste group that could differentiate it positively from groups traditionally regarded as being "higher" in the caste hierarchy. In political contexts, human beings are thus motivated to attenuate negative aspects of their ingroup's history, which has been starkly demonstrated in contexts of national guilt surrounding ingroup atrocities, for instance (Branscombe & Doosje, 2004).…”
Section: Social Identity Processesmentioning
confidence: 99%